Thermodynamic Analysis of Hybrid Absorption Compression System - Ramesh kumar, A; ., . (International Journal of Engineering and Technology, 2018)
The Virtual Reality realistic image content is a technology to enable building imaginary space by This paper presents thermodynamicÂ studies conducted on a GAX hybridÂ absorption-compression (HYBRID) cycle using ammonia-water as working ï¬‚uid for air-conditioning applications. The effect of generator, condenser and absorber temperatures on exergy destruction has been investigated. The effect of absorber pressure on the exergy destruction of the cycle has also been studied. It is found that generator and absorber are the major contributors in the total exergy destruction of the hybrid cycle. Comparison of hybrid cycle with conventional GAX cycle shows hybrid cycle has lower value of exergy destruction than the conventional GAX cycle. It is also found that at same thermal conditions assumed in this work the hybrid cycle gives 18 percent increases in average exergetic efficiency when compared to the conventional GAX cycle.Â Â Â